Prognostic value of longitudinal strain of subepicardial myocardium in patients with hypertension. Issue 6 (June 2016) - Lee, Wen-Huang; Liu, Yen-Wen; Yang, Li-Tan; Tsai, Wei-Chuan
Abstract : Objective: Global longitudinal strain is not well illustrated for the prognostic value in hypertension. This observational study investigated the prognostic value of global longitudinal strain, subendocardial longitudinal strain, and subepicardial (EpiLS) longitudinal strain in regularly treated hypertensive patients. Methods: Ninety-five hypertensive study participants (60.0% men, age 65.5 ± 12.0 years) were regularly treated for more than 1 year. We performed a two-dimensional echocardiographic study and obtained global peak systolic left ventricular longitudinal strain of subendocardial myocardium and the subepicardium (defined as subendocardial longitudinal strain and EpiLS, respectively). Cardiovascular events included cardiovascular death and any admission for stroke, acute coronary syndrome, or heart failure. Results: After a follow-up period of 7.3 ± 2.0 years, 20 (21%) study participants had cardiovascular events. Significant differences between study participants with and without cardiovascular events were noted in diuretic administration (75.0 vs. 93.3%, P  = 0.018), age (71.0 ± 11.6 vs. 64.0 ± 11.8 years, P  = 0.02) and EpiLS (−16.0 ± 2.0 vs. −17.7 ± 3.0%, P  = 0.04). Using multivariate Cox regression analysis, EpiLS was the only independent prognostic factor (hazard ratio 1.449, 95% confidence interval 1.027–2.045, P  = 0.035). Using the cut off value of −17.57% for EpiLS (median value of EpiLS), the Kaplan–Meier survival curve revealed a significant difference ( P  = 0.016) associated with cardiovascular outcome. Conclusion: EpiLS was the only independent prognostic factor in regularly-treated hypertensive patients. Our results indicated that involvement of subepicardial myocardium may infer worse prognosis of hypertensive heart disease.